Heat Tolerance, Energetics, and Thermal Treatments of Honeybees Parasitized With Varroa - Aldea-Sánchez, Patricia; Ramírez-Cáceres, Guillermo E.; Rezende, Enrico L.; Bozinovic, Francisco (Frontiers in Ecology and Evolution, 2021)
Ongoing global change affects both wildlife and economically relevant species, which are now subjected to combined challenges from climate change and higher exposure to pathogens. Honeybee colonies worldwide are under threat by higher temperatures and the ectoparasitic mite Varroa destructor, hence we studied the impact of these combined challenges in the thermal biology and energetics of Apis mellifera. We estimated the heat tolerance and energy expenditure (CO2 production, VCO2) of honeybees acclimated to different temperatures (32 and 38ºC) and subjected to different levels of parasitism (0, 1 and 2 mites). Heat tolerance was quantified employing thermal death time (TDT) curves describing how survival times vary as a function of temperature, which differed significantly between treatments. Warm-acclimated uninfected bees exhibited a higher thermal tolerance than their cold-acclimated counterparts, but parasitism by Varroa resulted in a substantial drop in tolerance rendering TDT curves of parasitized bees virtually indistinguishable. Accordingly, VCO2 increased dramatically in parasitized bees (46.5% and 67.1% with 1 and 2 Varroa, respectively), suggesting that Varroa impinges on substantial costs on energy expenditure which, in combination with lower fat reserves due to parasitism, should have synergistic effects on bees’ survival and performance. Results provide conclusive evidence of the detrimental impact of Varroa on heat tolerance that undermines potentially adaptive responses associated with thermal acclimation. Results also show that heat treatments are a realistic venue to control Varroa, and we discuss how TDT curves may be employed to optimize management strategies in this context.